1998
DOI: 10.1093/fampra/15.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of influenza symptomatology in elderly people

Abstract: It is recommended that the criteria of the Sentinel Stations in The Netherlands and the ICHPPC-2 be adapted in the following way: influenza is likely if, out of the entire complex of symptoms, at least fever, coughing and an acute onset occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
2
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 0 publications
11
121
2
4
Order By: Relevance
“…In outpatient studies, many recruitment strategies involve evaluating patients when they report ILI symptoms, such as fever and respiratory symptoms. [2][3][4][5][6] Not surprisingly, these studies observed high rates of fever and respiratory symptoms. Several reports have documented shortcomings of the definition of ILI in long-term care facilities, specifically because many patients did not have documented fever.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In outpatient studies, many recruitment strategies involve evaluating patients when they report ILI symptoms, such as fever and respiratory symptoms. [2][3][4][5][6] Not surprisingly, these studies observed high rates of fever and respiratory symptoms. Several reports have documented shortcomings of the definition of ILI in long-term care facilities, specifically because many patients did not have documented fever.…”
Section: Discussionmentioning
confidence: 87%
“…The difficulties of identifying influenza virus infection on the basis of clinical characteristics have been well described for outpatients, [2][3][4][5][6][7] patients in the emergency department, 8,9 and residents of nursing homes. 10 There are fewer recent data regarding the clinical presentation of hospitalized patients with influenza.…”
Section: Infect Control Hosp Epidemiolmentioning
confidence: 99%
“…A study in England of spatiotemporal analyses of telehealth data found that fever calls for 5-14-year-old children provided a timely and unique description of the evolution of a national influenza outbreak in England [12]. In studies comparing those with and without positive cultures for influenza virus, fever has been shown repeatedly to have better differentiating ability in comparison with other symptoms or combination of symptoms [18][19][20][21]. Also, patient self-reporting in the ED has been shown to be better than the chief complaint found in the medical chart for predicting the diagnosis made in the emergency room [22].…”
Section: Discussionmentioning
confidence: 99%
“…Sin desconocer lo anterior, es conocido que la infl uenza tiene diferentes presentaciones, la fi ebre algunas veces es baja y cardiopatías o condiciones pulmonares previas pueden confundir el diagnós-tico 7 . En ancianos, el cuadro clínico puede estar modifi cado y la triada fi ebre, tos, e inicio súbito tiene un valor predictivo de sólo 30%, mientras en el adulto joven llega a 78% 8 .…”
Section: Discussionunclassified